In‐depth peripheral CD4+ T profile correlates with myasthenic crisis. Issue 4 (22nd February 2021) - Huan, Xiao; Luo, Sushan; Zhong, Huahua; Zheng, Xueying; Song, Jie; Zhou, Lei; Lu, Jun; Wang, Ying; Xu, Yafang; Xi, Jianying; Zou, Zhangyu; Chen, Sheng; et al.
Abstract: Objective: Myasthenia gravis (MG) is an autoimmune disease caused by autoantibodies against neuromuscular junctions. Myasthenic crisis (MC) represents the most severe state of MG with high in‐hospital mortality. We aimed to identify immune signatures using in‐depth profiling in MC, and to assess the correlations between immune biomarkers with clinical severity longitudinally. Methods: We studied 181 participants including 57 healthy controls, 96 patients with MG who never experienced crisis and 28 MC patients from December 2018 through June 2020. Follow‐up visits occurred prospectively from crisis to 6 months off‐mechanical ventilation. The frequencies of 20 CD4 + T subpopulations and 18 serum cytokines were associated with clinical scores using correlations and principal component analysis. Results: Patients in crisis exhibited a proinflammatory CD4 + T response with elevated Th1 ( P  = 0.026), and Th17 cells ( P  = 0.032); decreased T follicular helper 2 (Tfh2) cells ( P  < 0.001), Tnaive in Tfh cells ( P  < 0.001), ICOS − Tfh cells ( P  = 0.017), and T central memory in Tfh ( P  = 0.022) compared with controls, and increased frequencies of Tregs ( P  = 0.026) and Tfh17 ( P  = 0.045) compared with non‐crisis MG. Cytokine cascade was identified in crisis including the ones associated with Th1 (IL‐1β/2/12p70/18/27/IFN‐γ/TNF‐α), Th2 (IL‐4/5/13), Th17 (IL‐6/17A/21/22/23/GM‐CSF), Th9 (IL‐9), and Treg (IL‐10). Longitudinally, seven immune biomarkers including Tregs, IL‐2/4/17A/IFN‐γ/TNF‐α/GM‐CSF had significant correlations with MG‐activities of daily living score. Interpretation: Vigorous inflammatory CD4 + T signatures were identified in MC and are associated with clinical severity. Future research is needed to explore its potential candidacy for therapeutic intervention and predicting impending crisis.